Al-Ahadeeth Which Are Uncorrected and Have Been Worked on A Critical study for Worships in, Jame' Al-Termezi - Amer Abd- Alfatah Joudallah (My University, 2011)
Jame' Al- Termezi, is considered as one of the most important and prominent among his classifications not only from Al-Hadeethiyah aspect but also from Al-Feqheyah Aspect and that is because Al-Emam concerned in finding Al-Ahadeeth in his Jame', which have been worked on regardless if they are correct or weak . Many studies have been written about Al-Imam and his Jame' ,except one of these studies has not talked about weak Ahadeeth which have been mentioned in Al-Imam and his Jame' and worked on by other scientists and showing their reasons in doing that. As a result, the aim of this theses is to study weak Ahadeeth and to show the reasons that have been justified by scientists to work on them by using a critical study, as well as using the scientific discussion for these reasons and supporting my view with applied evidences. The research was able from this study to find the nine reasons which made scientists to work on the Ahadeeth which haven't been mentioned in the Jame' Al-Termezi and they are the following: 1-Some scientists ‘objections about weak Ahadeeth when there is just the same issue. 2-Some scientists' objections about Good Actions. 3-Some scientists' objections such as Al- Imam Abo-Honaifah and Malik 4-Some scientists' objections about weak Ahadeeth due to their agreement with the sayings of some of A- Sahabah ,particularly when sayings are about opinions related to worships that are always true. 5-Science Acceptance for one of these Ahadeeths by acceptance . 6-When the Ahaddeth agree with the texts mentioned in the Holy Qura'n and Al- Sunnah Al-Saheehah. 7-When the Ahadeeths modified by multiplicity of methods. 8-When the Ahadeeths mentioned in another right source except Jame' Al- Termezi 9-When Al- Termezi weakens the Hadeeth and agreed the condition of of correction by some scientists particularly Al-Fuqaha' that is because their conditioned in corrections and weakness differ from Al- Mohadetheen conditions. In conclusion, the researcher has done an evaluative study and has discussed these reasons and has led him to the following: 1-The supporting for some of these reasons to work on weak Ahadeeths when they are strengthened by many methods or agreed the sayings of Al-Sahabah ,or mentioned in another source or agreed the general right texts. 2-Criticism and directing other reasons.

يعدُّ (جامع الترمذي) من أبرز مصنفات الحديث النبوي، ومن أعظمها أهمية، ليس من الناحية الحديثيَّة فقط، وإنِّما من الناحية الفقهية كذلك؛ ذلك أنَّ الإمام الترمذي عُنِيَ بأنْ يُخَرِّجَّ في (جامعه) الأحاديث التي عليها العمل عند العلماء، أو بعضهم، سواءً أكانت صحيحة أم ضعيفة. وقد كُتبت دراساتٌ عديدة عنيت بالإمام الترمذي و(جامعه)، بيد أنْ أياً من تلك الدراسات لم تتطرق لدراسة الأحاديث الضعيفة التي أوردها الترمذي في (جامعه)، وَعمِل بها العلماء، وبيان أسباب عمل العلماء بتلك الأحاديث، ومن هنا فقد جاءت هذه الأطروحة لتدرس تلك الأحاديث، وتبين -من خلال الدراسة النقدية- الأسباب التي سوّغت للعلماء العمل بهذه الأحاديث، مع المناقشة العلمية لهذه الأسباب، ودعم ذلك من خلال إيراد الأمثلة التطبيقية. وقد استطاع الباحث من خلال الدراسة الوصول إلى تسعة أسبابٍ دَعَتْ العلماء للعمل بالأحاديث التي لم تصح في (جامع الترمذي)، وهذه الأسباب، هي: 1-احتجاج بعض العلماء بالضعيف إذا لم يرد في المسألة غيره. 2-احتجاج بعض العلماء بالحديث الضعيف في فضائل الأعمال. 3-احتجاج بعض العلماء كالإمامين أبي حنيفة ومالك، بالحديث المرسل. 4-احتجاج بعض العلماء بالأحاديث الضعيفة لموافقتها أقوال بعض الصحابة، خاصة إذا كانت أقوال الصحابة مما لا مجال فيه للرأي كأحاديث العبادات. 5-تلقي العلماء لبعض هذه الأحاديث بالقَبول. 6-موافقة الحديث النصوص العامة من القرآن الكريم والسنة الصحيحة. 7-تصحيح الحديث بمجموع الطرق. 8-ورود الحديث من طريقٍ آخر صحيح غير الطريق الذي أخرجه منه الترمذي. 9-إذا ضَعَّف الترمذي الحديث، وقد وافق هذا الحديث شرط التصحيح عند بعض العلماء خاصةً الفقهاء، حيث إنَّ شروطهم في التصحيح والتضعيف تختلف عن شروط المحدثين. وبعد بيان هذه الأسباب، قام الباحث بدراسة لها؛ ناقش من خلالها هذه الأسباب، وقد قادته هذه المناقشة إلى: 1-تأييد بعض هذه الأسباب كالعمل بالضعيف إذا تقوى بمجموع الطرق، أو وافق أقوال الصحابة، أو ورد بإسناد آخر صحيح، أو وافق عموم النصوص الصحيحة. 2-نقد الأسباب الأخرى وتوجيهها.
الأحاديث التي لم تصح وعليها العمل، دراسة استقرائية نقدية لأبواب العبادات في جامع الترمذي